IMPLEMENTASI PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI BERBASIS CINTA DALAM MEMBENTUK KARAKTER RELIGIUS SISWA KELAS XII DI SMA NEGERI 1 LEUWILIANG KABUPATEN BOGOR - Elsa Juita; Rumba Triana; Wartono Wartono (STKIP Pesisir Selatan, 2026)
This study examines the implementation of love-based Islamic Religious Education (PAI) and Characteristics learning for grade XII students at SMAN 1 Leuwiliang, Bogor Regency, focusing on its role in shaping religious character along with its supporting and inhibiting factors. Utilizing a qualitative case study approach, data were gathered through observation, documentation, and in-depth interviews with teachers and students, then analyzed using an interactive model. The results reveal that love-based pedagogy (loving pedagogy) is systematically implemented through humanistic communication, comfortable learning environments, interactive methods, and moral role-modeling. This approach successfully transforms student behavior by enhancing discipline in congregational prayers, activating Quranic recitation, and strengthening courtesy toward teachers and peers. Although digital distraction from gadgets poses a challenge, it is successfully mitigated through intensive personal guidance and sustainable spiritual advice. This study provides a distinct novelty by demonstrating that love-based pedagogy, typically associated with Islamic institutions under the Ministry of Religious Affairs, can be effectively managed within public high schools under the Ministry of Primary and Secondary Education to counter the youth moral crisis.